A review of biological aerated filters for iron and manganese ions removal in water treatment. (June 2018) - Marsidi, Nuratiqah; Abu Hasan, Hassimi; Sheikh Abdullah, Siti Rozaimah
Graphical abstract: Highlights: A review on treatment technology for Fe and Mn removal. The effect of high Fe and Mn in water to human. Key operational principles of BAF system for Fe and Mn removal. Possible challenges of Fe and Mn removal using BAF systems. Potential microorganisms as remediating agents in a BAF system. Abstract: Water contains iron (Fe) and manganese (Mn) that can be difficult to remove by singular physico-chemical methods This review paper focuses on the potential of biological aerated filter (BAF) technology for the simultaneous removal of Fe and Mn. It also covers the chemical properties of the respective metals, the causes and effects of high Fe and Mn, and other removal technologies including conventional and advanced treatment methods Surface waters and groundwater aquifers contain concentrations of Fe and Mn above their permitted limits as regulated by the authorities. Thus, the BAF system and its features are believed to have much potential to overcome many of the problems related to Fe and Mn contamination.